Nationale Versorgungsleitlinie (NVL) Diabetische Retinopathie: 2. Auflage der NVL zur Therapie der diabetischen Retinopathie = National guidelines for treatment of diabetic retinopathy - Ziemssen, Focke; Hammes, Hans-Peter (Der Ophthalmologe, 2016)
The updated German clinical practice guidelines (second edition) describe the consensus recommendations for prevention and treatment of retinal complications secondary to diabetes. According to the updated numbers on epidemiology a further increase of persons affected is expected. The prevalence of diabetic retinopathy is estimated to be 9-16 % in type 2 diabetes and 24-27 % in type 1 diabetes. A prolongation of the screening interval from 1 to 2 years is recommended for those patients with a lower risk of progression, when retinopathy has not already occurred and no increased systemic risk factors are present. Standardized documentation forms are the foundation for improved communication between the disciplines. If diabetic retinopathy is present, control examinations follow the stipulations of the ophthalmologist. The guidelines define scenarios when the use of optical coherence tomography (OCT) is necessary, e. g. diagnosis and follow-up of macular edema. Besides focal and panretinal laser therapy, the efficacy and risks of intravitreal operative pharmacotherapy are discussed. Focal laser coagulation is recommended for therapy of macular edema without foveal involvement and for macular edema with foveal involvement patients should be informed about the effective alternative forms of treatment. Panretinal laser coagulation is recommended for first line treatment of proliferative diabetic retinopathy and is optional for severe non-proliferative retinopathy.